A társadalmi tradíció és progresszió folyamatainak kapcsolódása az északkeleti régió vállalkozásaiban - Láczay, Magdolna (Közép-Európai Közlemények, 2014)
The social processes of borderline minor villages have developed unique formations since the regime change in Hungary. Initially they were realised in the creation of forced enterprises and lateron in the modern forms of the so-called social enterprises of local authorities. Hereby I examine the survival of traditional social values on its complexity by the more popular integration approaches of historical and management sciences. In minor settlements local entrepreneurs, even mayors, who were earlier considered to use outdated methods, adapt their previous knowledge and traditions to the organization and management of their present enterprises. They mostly employ communal workers or unemployed ones for these traditional agricultural enterprises. As for the schools of management, contingency theories seem to provide us with the combination of methods of the fields of sciences, which focus on the question whether the phenomenon can be considered progressive.